An evaluation of the economics and productivity of fully mechanised tree seedling planting in Brazil. Issue 3 (3rd July 2019) - Guerra, Saulo Philipe Sebastião; Soler, Rafael Ribeiro; Sereghetti, Guilherme Corrêa; Oguri, Guilherme
Abstract : From an economic point of view, Eucalyptus is the most important forest genus in Brazil, covering more than 5 million ha. However, most of the silvicultural practices have a low level of mechanisation compared with harvesting and logging operations. This study presents an evaluation of the economics and productivity of the first Brazilian experience of using a planter device attached to an excavator boom while performing eucalypt seedling planting. A classic time-and-motion study was performed on two commercial tree spacings to evaluate the economic efficiency. Considering the final cost of planted seedlings, the wider spacing was 17% higher than narrower spacing, due to a higher productivity: 355 and 324 seedlings per productive machine hour (pmh), respectively. Total cost was 66.84 € pmh −1 and 0.21 € planted seedling −1 with wider spacing.